Polydopamine grafting polyether ether ketone to stabilize growth factor for efficient osteonecrosis repair - Yi Sun; Jingyun Liu; Kaijia Chen; Nannan Zhong; Chengpeng He; Xinming Luan; Xiaobei Zang; Jianbo Sun; Ning Cao; Wenbo Wang; Qiang Ren (Scientific Reports)
Abstract This study examines the biocompatibility, osteogenic potential, and effectiveness of polyether ether ketone (PEEK) composites for treating osteonecrosis, seeking to establish a theoretical basis for clinical application. A range of PEEK composite materials, including sulfonated polyether ether ketone (SPEEK), polydopamine-sulfonated polyether ether ketone (SPEEK-PDA), bone-forming peptide-poly-dopamine-sulfonated polyether ether ketone (SPEEK-PDA-BFP), and vascular endothelial growth factor-poly-dopamine-sulfonated polyether ether ketone (SPEEK-PDA-VEGF), were constructed by concentrated sulfuric acid sulfonation, polydopamine modification and grafting of bioactive factors. The experiments involved adult male New Zealand rabbits aged 24–28 weeks and weighing 2.6–4 kg. The SPEEK-PDA-BFP possesses the smallest water contact angle, indicating the highest hydrophilicity, with its surface characterized by a rich density of clustered BFP particles. The SPEEK-PDA-BFP exhibits superior adhesion, proliferation, and differentiation capabilities, along with pronounced bacteriostatic effects, which are attributed to its dense particle clusters. The SPEEK-PDA-BFP facilitates the formation of regular and dense bone trabeculae. Comparative study on treating osteonecrosis with SPEEK-PDA-VEGF and SPEEK-PDA-BFP highlighted the superior formation of mature bone trabeculae and angiogenic protein CD31 around SPEEK-PDA-VEGF. The PEEK composite materials have good biocompatibility, osteogenic activity and bone repair activity. In particular, SPEEK-PDA-VEGF composite materials have the best effect on bone repair.